PEMBERIAN REWARD DAN DAMPAKNYA TERHADAP KREATIFITAS KARYAWAN - Amiruddin, Rizal; Muslimin, Rustan (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2025)
In the field, the phenomenon shows that companies are increasingly realizing the importance of employee creativity in driving innovation and competitive advantage. One effort is providing rewards to show appreciation for performance. However, the effectiveness of rewards in increasing creativity remains a question that requires further research. The study aims to analyze the effect of rewards on employee creativity. The research method used is a quantitative approach with Simple linear regression analysis technique. Data were collected through distributing questionnaires to a number of Bazarnas Gorontalo employees and analyzed statistically. The results showed that the reward variable (X) had a positive but insignificant effect on employee creativity (Y), as indicated by the calculated T value of 0.442 and a significance value of 0.661 (≥ 0.05). Thus, it can be concluded that although reward provides a positive impetus, it is not significant enough to increase employee creativity in the context of the organization under study.